The main provisions of the program on improvement technique of competitive actions qualified foil fencers at a stage of specialized basic training - Bakum A.V (Kharkov National Pedagogical University, 2012)
A ground and program of perfection of technique of competition actions of skilled sportsmen is presented in setup and competition times of annual cycle of preparation. 14 sportsmen took part in an experiment. The program was based on programmatic-having a special purpose approach and included the models of competition actions. The program included the complexes of physical exercises, directed on perfection of basic elements of technique of attacking, protective and counter-attacking actions also. Program components are included by complexes: imitation, tricking into, specially-preparatory and competition physical exercises of the having a special purpose affecting separate elements of technique of battle actions. Gradual complication of terms of implementation of exercises is recommended without an opponent, with a conditional opponent, with a partner and individual lessons.